2020
DOI: 10.1186/s12884-020-03100-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between prepregnancy body mass index and risk of congenital heart defects in offspring: an ambispective observational study in China

Abstract: Background: Congenital heart defects (CHDs) are the most common birth defect around the world. Maternal prepregnancy obesity has been proposed as a risk factor of CHDs, but the relationship of CHD risk with over-and underweight is controversial, especially because body mass index (BMI) distribution differs between Asia and the West. The study aimed to examine the potential associations of maternal over-and underweight on risk of offspring CHDs. Methods: An ambispective observational study involving 1206 fetuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A total of 32 publications were included in the review ( Table 1 and S3 Table ). Among these, 17 dealt with maternal overweight or obesity [ 14 , 15 , 19 , 29 42 ], 10 dealt with pre-gestational diabetes (PGDM) [ 16 18 , 40 , 41 , 43 47 ], four dealt with DM1 [ 13 , 19 , 48 , 49 ], two dealt with DM2 [ 19 , 48 ], eight dealt with GDM [ 16 18 , 39 41 , 46 , 49 ], four dealt with hypertension [ 19 , 20 , 43 , 48 ], three dealt with PE [ 21 , 22 , 50 ], and none were about dyslipidaemia or MetS (as a diagnostic category). Except for the combination of PGDM and GDM, six studies investigated more than one maternal metabolic disorder (but not in combination) [ 19 , 39 41 , 43 , 48 ], and one study assessed a combination of two conditions (obesity and GDM) and the risk of CHDs [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 32 publications were included in the review ( Table 1 and S3 Table ). Among these, 17 dealt with maternal overweight or obesity [ 14 , 15 , 19 , 29 42 ], 10 dealt with pre-gestational diabetes (PGDM) [ 16 18 , 40 , 41 , 43 47 ], four dealt with DM1 [ 13 , 19 , 48 , 49 ], two dealt with DM2 [ 19 , 48 ], eight dealt with GDM [ 16 18 , 39 41 , 46 , 49 ], four dealt with hypertension [ 19 , 20 , 43 , 48 ], three dealt with PE [ 21 , 22 , 50 ], and none were about dyslipidaemia or MetS (as a diagnostic category). Except for the combination of PGDM and GDM, six studies investigated more than one maternal metabolic disorder (but not in combination) [ 19 , 39 41 , 43 , 48 ], and one study assessed a combination of two conditions (obesity and GDM) and the risk of CHDs [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of the 32 studies are presented in Table 1 and S3 Table . Three examined populations of non-European descent (Taiwan and China) [ 39 , 42 , 48 ]. Half of the studies reported results from livebirths only; eight studies had populations including both singleton and multiple births; and 11 studies did not state whether they included only singleton or multiple births.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this nding contrasts with previous studies in China. Xuelian [21] et al reported that the risk of CHDs was signi cantly higher among mothers with prepregnancy underweight and low-average BMI, and they failed to observe any signi cant relationships between prepregnancy overweight or obesity and the risk of CHDs in offspring, even when using different cut-off values to de ne reference groups. This difference may be due to the relatively small number of overweight women in their study.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis involving 99,205 CHDs cases among 6,467,422 participants reported that increased maternal BMI was associated with the risk of developing CHDs in offspring [20] . However, some failed to observe any signi cant relationships between prepregnancy obesity and the risk of CHDs [21] .…”
Section: Introductionmentioning
confidence: 99%